2018
DOI: 10.4034/pboci.2018.181.20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Frenum Morphology and Attachment in Malaysian Children

Abstract: To determine the prevalence of various types and attachment level of maxillary frenum in Malaysian children. Material and Methods: A cross-sectional study was conducted in a total of 200 children of age ranging from 2 to 15 years. Photographs of maxillary frenum were taken and their types and level of attachment were recorded by using Placek's classification and modified Sewerin typology. Children were divided into 3 groups based on age: between 2-5, 6-11 and 12-15 years. Descriptive analysis was carried out t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
4
4
0
Order By: Relevance
“…Many studies have reported the simple frenum to be the most common type with differences in other types based on Sewerin's classification. 5,14,18,21,27 In line with our results, Rathod et al reported simple frenum as most common type followed by frenum with nodule and frenum with appendix. 15 However study done by Nagavent et al 27 and Birader et al 28 the persistent tectolabial frenum was the common type after simple frenum.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Many studies have reported the simple frenum to be the most common type with differences in other types based on Sewerin's classification. 5,14,18,21,27 In line with our results, Rathod et al reported simple frenum as most common type followed by frenum with nodule and frenum with appendix. 15 However study done by Nagavent et al 27 and Birader et al 28 the persistent tectolabial frenum was the common type after simple frenum.…”
Section: Discussionsupporting
confidence: 88%
“…These studies have related their findings based on age, gender, race, and ethnicity. 10,14,15,[18][19][20] Inconsistent to our study, mucosal frenal attachment was to be prevalent in studies done by Kotian et al, 18 Pandian et al 21 We also observed similar findings based on Mirko's classification of maxillary labial frenum according to location.…”
Section: Discussionsupporting
confidence: 87%
“…The distribution of frenal attachment types according to age showed that mucosal and gingival frenal types were noticed in patients aged between 13-15 y, while 12 years old children had a higher distribution of papillary frenal types. These results conformed with Divater et al, 2019;Zakirulla et al, 2021 and can be related to the tendency of the labial frenum to migrate more apically with aging (Pandiyan and Hedge, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Bifid type frenum prevalence was seen as 8.8% in all of the age groups and when compared to the other groups the highest prevalence was seen in the GI group (18.3 %). A decrease in There are studies indicating that the MMLF gingival type is seen at a high rate (30.0-61.0 %) (2)(3)(4)8,15,18), as well as studies indicating that the mucosal type is detected (6,10,14,17,19). We attribute the reason for this difference to the age range of the selected population and the limited sample size.…”
Section: Resultsmentioning
confidence: 99%